2020
DOI: 10.3174/ajnr.a6444
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Cancer: Evaluation of MR Imaging Grading Systems in Patients with Suspected Nasopharyngeal Carcinoma

Abstract: BACKGROUND AND PURPOSE:We evaluated modifications to our contrast-enhanced MR imaging grading system for symptomatic patients with suspected nasopharyngeal carcinoma, aimed at improving discrimination of early-stage cancer and benign hyperplasia. We evaluated a second non-contrast-enhanced MR imaging grading system for asymptomatic patients from nasopharyngeal carcinoma plasma screening programs. MATERIALS AND METHODS:Dedicated nasopharyngeal MR imaging before (plain scan system) and after intravenous contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is a noninvasive tool used for differentiating NPC T1 and BH (5). However, the diagnostic accuracy of MRI is limited for these 2 entities due to the considerable overlap of MRI features such as diffuse symmetrical wall thickening of the nasopharynx (1,(6)(7)(8). Moreover, the wider application of MRI is limited by its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is a noninvasive tool used for differentiating NPC T1 and BH (5). However, the diagnostic accuracy of MRI is limited for these 2 entities due to the considerable overlap of MRI features such as diffuse symmetrical wall thickening of the nasopharynx (1,(6)(7)(8). Moreover, the wider application of MRI is limited by its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an updated MRI grading system has been recently prsoposed 17 with the primary aim of improving specificity to decrease the biopsy referral rate of subjects without NPC (Supporting Table 2). The updated system is expanded from 4 to 5 grades, with grades 4 and 5 indicating NPC and referral for biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as a higher proportion of the population in NPC‐endemic areas participates in periodic screening, there is a need to understand whether the performance of endoscopic examination differs between individuals who are undergoing screening for the first time and those who are participating in a second or subsequent round of screening because the techniques used to diagnose NPC in subsequent screening rounds will likely need to be sufficiently sensitive to detect small, incipient tumors. Uncertainties exist about whether small tumors present beneath the mucosa surface and whether those in difficult‐to‐visualize areas of the pharyngeal recess (fossa of Rosenmüller) might be missed by endoscopy 13‐17 . Because of the potential limitations of endoscopy, other diagnostic approaches such as magnetic resonance imaging (MRI) have been suggested as alternative NPC detection tools 15‐20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unlike the previously reported MRI studies of primary NPC delineation by CNNs in the literature (9)(10)(11)(12)(13)(14), this study evaluated the delineation performance on the non-contrast-enhanced T2weighted fat-suppressed (NE-T2W-FS) sequence rather than the contrast-enhanced T1-weighted sequence. This sequence was chosen to support our ongoing research into early NPC detection by MRI (15)(16)(17) in which we are developing a low-cost MRI protocol for NPC Epstein-Barr virus DNA screening programs that does not require the injection of an MRI contrast agent (18,19). Our previous study has also shown the NE-T2W-FS sequence is promising for primary NPC delineation with CNN (20), but the general-purpose CNN tested in that study would benefit from customisations.…”
Section: Introductionmentioning
confidence: 99%